Formulation and Evaluation of a Polyherbal solution and green synthesis of ZnNPS against metabolic disorder associated with experimental diabetes in rats - BEN MOUSSA Ouissam (Université of Eloued جامعة الشهيد حمه لخضر, 2021)
Our study aimed to investigate the effect of polyherb (formulated by some plants) and ZnNPs (formulate by green synthesis) on physiological, biochemical alterations and oxidative stress induced by experimental diabetes in rats. For this purpose, 24 female albino Wistar rats were randomly divided into 6 groups (n=4); healthy rats (Control), healthy rats treated with polyherb (Polyherb), healthy rats treated with ZnNPs (ZnNPs), diabetic rats (Diabetic), Diabetic rats treated with polyherb (D+Plyherb) and Diabetic rats treated with ZnNPs (D+ZnNPs). All types of treatments were given to rats orally for 21 days. Diabetic in rats was induced by single dose intaperitonially administration of Alloxan (150mg/kg). Various parameters as hematological, biochemical and oxidative stress markers were estimated. Histopathologies of pancreas tissues were observed. In in-vitro study on plant and nanoparticles, some quantitative, qualitative and characterization parameters were analyzed using standard protocols. In vitro phytochemical analysis results revealed that polyherb contains phenols, flavonoids, alcaloids, terpenoids, tannins and steroids. In vivo results, in diabetic group showed an alteration in lipid profile and biochemical parameters. While, the antioxidant defends system in liver, kidney, pancreas, ovary were affected by increasing the MDA level and decreasing the GSH levels and SOD activities compared to control. Moreover, the hematological parameters revealed that Diabetes induce an anemia in rats by a significant diminution (P<0.01) of RBC, MCV and HCT levels. In the other hand, histopathological analysis noted an alteration in pancreas tissues of diabetic rats group compared to control. However, the treatment of Diabetic rats by Polyherb and ZnNPs ensured a partial amelioration and correction of the previous parameters. In conclusion, the use of Polyherb and Nanoforme of zinc appears to be the dominant limited of development and complication of diabetes which can have a benefic effect against others diseases which oxidative stress plays an important role
Applied Biochemistry
Keywords: Diabetes; Oxidative stress; Polyherb; ZnNPs; Rats; الإجهاد; مرض السكري; المحلول العشبي; التأكسدي